Faktor-Faktor yang Mempengaruhi Produktivitas Pekerja Pada Industri Kerajinan Sanggah di Desa Jehem Kabupaten Bangli - Sentana, Wisnu; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Increased productivity is an important thing. Increased productivity will affect the increase in labor income and also increase the family income. So the increase in productivity has a positive impact on the level of social welfare. Jehem village Bangli district is an area of study where as many as 67 craftsmen as the sample used. Increase the productivity of workers in the craft industry protested in the village of Bangli regency Jehem is the purpose of this study. Structured interviews (questionnaires), in-depth interviews and non-participant observation is the data collection techniques used. Technique using multiple linear regression analysis where. Age, work experience and technology simultaneously significant effect on the productivity of workers in the craft industry in the village protested Jehem Bangli regency, is supported by the value of R Square = 0.779 means that 77.9 per cent of the rise and fall in the productivity of workers protested in the village handicraft industry Jehem District Bangli is influenced by age, work experience, and technology, the remaining 22.1 percent is influenced other variables. In partial, age, work experience, and technology and significant positive effect on the productivity of workers in the craft industry protested in the village of Bangli regency Jehem
Keywords: umur; pengalaman kerja; teknologi; produktivitas